Philosophy of Education and Character Education Management: Building the Morality of the Young Generation Through Sport - Susanti, Rahayu; Ahmad, Masduki; Suryadi, Suryadi (Journal Coaching Education Sports, 2025)
The development of technology and digitalization in the Industrial Age 4.0 brings new challenges in character education, especially in shaping the morality of the younger generation who are exposed to the rapid flow of information and social change. This article aims to analyze the role of philosophy of education as a conceptual foundation in character education management to form a young generation with morality, integrity, and responsibility. Through an interdisciplinary approach that incorporates values from various schools of educational philosophy such as humanism, existentialism and pragmatism, this article highlights how these values can be applied in school policies, curriculum and learning methods. This research uses a qualitative method with literature analysis and case studies on several schools that implement philosophy-based character education. The results show that philosophy-based character education management is able to shape students with deeper moral understanding and stronger ethical awareness in the use of technology. Challenges faced include teachers' limited understanding of educational philosophy and the lack of structured policy support. Nevertheless, philosophy-based character education proved to be more effective in building long-term morality than conventional approaches that focus on reward and punishment.